Social Issues in Digital Collage - Buraq Ali Ahmed Alawadi (International Consortium of Education and Culture Research Studies, 2025)
General Background: Digital collage has emerged as a significant contemporary visual art practice within the development of digital technology, photography, and surrealist aesthetics. Specific Background: The integration of photographic imagery, layered composition, and digital manipulation has enabled artists to construct visual narratives related to feminism, politics, urban life, metaphysics, and cultural transformation through contemporary collage practices. Knowledge Gap: However, studies examining the relationship between digital collage and aesthetic photographic imagery, particularly in relation to social and political representation, remain limited. Aims: This study aims to identify the conceptual foundations of digital collage and photographic art while analyzing how digital collage constructs aesthetic and social meanings in selected international artworks produced between 2010 and 2016. Results: Using a descriptive analytical method through content analysis, the study found that digital collage operates as a dynamic visual medium that combines surreal composition, photomontage, juxtaposition, and layered imagery to create alternative realities and symbolic interpretations. The analyzed works by Eugenia Loli, Jesse Treece, Danai Gkoni, and Elizabeth Zvonar demonstrate that digital collage communicates themes of identity, feminism, political critique, urban crisis, metaphysics, and consumer culture through digitally manipulated photographic forms. Novelty: The study highlights digital collage as a conceptual and aesthetic framework that merges photography, digital technology, and social commentary within contemporary visual culture. Implications: These findings contribute to visual art and media studies by expanding understanding of digital collage as an innovative medium for artistic experimentation, social critique, and contemporary photographic representation. Highlights: • Digital montage combines surreal imagery with contemporary cultural narratives.• Selected artworks present feminism, urban crisis, and metaphysical symbolism visually.• Layered photographic composition creates alternative realities within contemporary visual culture. Keywords: Digital Collage, Photographic Imagery, Visual Art, Surrealism, Social Issues